The Shore Road Mystery - Dixon Franklin W.; Franklin W. Dixon (Canada Franklin W. Dixon, 1947)
Frank and Joe Hardy investigate a smuggling ring using a mysterious ship to transport contraband like counterfeit documents and illegal cargo.
Keywords: demonstrate a "never give up" attitude while investigating a smuggling ring; persistence, bravery, and teamwork can overcome even the most daunting, dangerous obstacles